Development of a prototype application to detect bad behaviour pattern / Mohamad Khairul Firdhaus M. Dollah - M. Dollah, Mohamad Khairul Firdhaus (2008)
Bad behaviour can be prevented by knowing their behaviour patterns before the problem occurs. Data mining is one way that can help in predicting or identifying the patterns behavior of certain individual that is involved in terrorist activity. Data mining is a process of finding hidden information and patterns in databases. One of the tasks for data mining purposes is classification refers to assigning cases into categories based on a predictable attributes. This method can be applied to detect patterns of bad behaviour UiTM students. By using auto discretization and rules compositions based on table and decision tree, classification method of data mining can be applied to the prototype application.